Learning Motivation, Self-Regulated Learning, And Mathematical Communication Skills Verbal And Written By Students' In Learning Mathematics During The Covid-19 Pandemic - Efriyadi, Dodi; Nurhanurawati, Nurhanurawati (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
This study aims to determine (1) how the learning motivation, self-regulated learning and verbal mathematical communication skills of students; and (2) how are students' learning motivation, self-regulated learning and mathematical communication skills in writing mathematics learning during the covid-19 pandemic. The research used is a mixed method type Sequential Exploratory Design. The population is students of class XI IPA SMA Negeri 1 Pringsewu. Data was collected using questionnaires, observations, documentation and written mathematical communication skills tests. The results of the study show that learning mathematics during the Covid-19 pandemic where learning motivation and self-regulated learning directly affect students' written mathematical communication skills, but verbal mathematical communication skills really need to be considered because they are still in the low category.Penelitian ini bertujuan untuk mengetahui (1) bagaimana kemampuan komunikasi matematis secara lisan peserta didik; dan (2) bagaimana motivasi belajar, kemandirian belajar dan kemampuan komunikasi matematis secara tulis peserta didik dalam pembelajaran  matematika pada masa pandemi covid-19. Penelitian yang digunakan adalah mixed methods tipe Sequential Exploratory Design. Populasi dalam penelitian ini adalah peserta didik kelas XI IPA SMA N 1 Pringsewu. Pengumpulan data menggunakan kuesioner, observasi, dokumentsi dan tes kemampuan komunikasi matematis tulis. Hasil penelitian menunjukkan pembelajaran matematika selama pandemi Covid-19 dimana motivasi belajar dan kemandirian belajar mempengaruhi secara langsung kemampuan komunikasi matematis secara tulisan peserta didik, tetapi kemampuan komunikasi matematis secara lisan sangat perlu di perhatikan karena masig tergolong dalam kategori rendah.